Constructing Identity among Chinese American through Jean Kwok Novels Mambo in Chinatown: Postcolonial Study - Melly Andani; Elin Eprilin Fitrian Miela Putri (Universitas Gadjah Mada, 2023)
This study aims to see how Chinese American people as immigrants in America construct their identity while facing two different cultures in society. This research is a descriptive qualitative study and using postcolonial approach. This study used novel by Mambo in Chinatown by Jean Kwok as the main data. Another document, journal, and author’s interview as the secondary data. Ambivalence by Homi K. Bhabha will used as the main theory of this research. The main data collected after the researcher goes through close reading of the novel. The result of this study show that ambivalence occur through this novel. This study also highlights that the struggle of the character in the novel reflect the reality life of Chinese American immigrant in America. Seen from their arrival in America and how the first-generation immigrant transferring Chinese culture and value to their children as the second-generation in America.